The Effect of Taxes on Transfer Pricing on Tourism, Restaurant, and Hotel Companies Listed on the Indonesia Stock Exchange In 2019-2020 - Nur Rohmah, Tri (Green Publisher Indonesia, 2022)
Transfer pricing by multinational companies is driven by tax or non-tax reasons. Along with the times, practice Transfer pricing is often done to minimize the amount of tax that must be paid. The growing tax burden triggers companies to carry out transfer pricing in the hope of suppressing the load. Transfer pricing in the sale of goods or services. This research on profitability aims to examine the effect of taxes on transfer pricing. The population in this research are tourism, restaurant, and hotel companies listed on the Indonesia Stock Exchange in 2019 - 2020. The sample in this research was selected through purposive sampling, so that a sample of 31 companies was obtained. The statistical test tool uses multiple regression analysis. Taxes in this research was measured by the effective tax rate (ETR), while transfer pricing was measured using dummy criteria. The dummy criteria used is a value of 1 if the company makes a sale transaction to a third party special, while the value 0 for entities that are not make sales to special parties. The results show that taxes has positive and insignificant effect on transfer pricing.